Sei sulla pagina 1di 6

# Eshelby Tensor

## (from Chapter 2, Micromechanics of Defects in Solids, T. Mura, 1987)

In class, we have shown that the strain inside inclusion is

ij = Sijkl kl*
where S ijmn = S jimn = S ijnm is called the Eshelby tensor. It is a function of the elastic properties
of the solid and the geometry of the ellipsoid. Generally, elliptic integrals are involved to calculate
the components of the Eshelby tensor. For isotropic solids,

S1111 =

3
1 2
a12 I11 +
I1
8 (1 )
8 (1 )

S1122 =

1
1 2
a22 I12
I1
8 (1 )
8 (1 )

S1133 =

1
1 2
a32 I13
I1
8 (1 )
8 (1 )

S1212 =

a12 + a22
1 2
( I1 + I 2 )
I12 +
16 (1 )
16 (1 )

All other non-zero components are obtained by the cyclic permutation of (1, 2, 3) . The
components which cannot be obtained by the cyclic permutation are zero; for instance,

## S1112 = S1223 = S1232 = 0 .

Assume a1 > a2 > a3 ,

I1 =

I3 =

4 a1a2 a3

(a

2
1

(a

)(

4 a1a2 a3

2
2

)(

## a32 a12 a32

12

{F( , k ) E( , k )}

a a 2 a 2
2 1
3

a
a

1 3

12

12

E( , k )

## where F( , k ) and E( , k ) are elliptic integrals defined as

F( , k ) = 1 k 2 sin 2

E ( , k ) = 1 k 2 sin 2
0

1 2

12

1
2
1
3
12

## The remaining I -functions follow from the identities:

I1 + I 2 + I 3 = 4
3I11 + I12 + I13 = 4 a12
3a12 I11 + a22 I12 + a32 I13 = 3I1

## I12 = (I 2 I1 ) a12 a22

The components of Eshebly tensor become elementary functions for special shapes of inclusions,
as listed below.
Sphere ( a1 = a2 = a3 = a ):

I1 = I 2 = I 3 = 4 3
I11 = I 22 = I 33 = I12 = I 23 = I 31 = 4 5a 2

7 5
15(1 )

## S1212 = S 2323 = S3131 =

5 1
15(1 )

4 5
15(1 )

or

S ijmn =

5 1
4 5
( im jn + in jm ) (see classnotes)
ij mn +
15(1 )
15(1 )

## The stress inside the inclusion is

11 =

16
5 + 1 *
5 + 1 *
11* 2
22 2
33
15(1 )
15(1 )
15(1 )

12 = 2

7 5 *
12
15(1 )

All other stress components are obtained by the cyclic permutation of (1, 2, 3) .

Elliptic cylinder ( a3 ):

I1 =

4 a2
4 a1
, I2 =
, I =0
(a1 + a2 )
(a1 + a2 ) 3

I12 =

4
4
4
, 3I11 = 2 I12 , 3I 22 = 2 I12 , I13 = I 23 = I 33 = 0
2
a1
a2
(a1 + a2 )

## a32 I13 = I1 , a32 I 23 = I 2 , a32 I 33 = 0

S1111 =

1 a22 + 2a1a2
a2
+ (1 2 )

2
2(1 ) (a1 + a2 )
a1 + a2

S 2222 =

1 a12 + 2a1a2
a
+ (1 2 ) 1

2
2(1 ) (a1 + a2 )
a1 + a2

S3333 = 0
S1122 =

1 a22
a2
(1 2 )

2
2(1 ) (a1 + a2 )
a1 + a2

S 2233 =

1
2 a1
2(1 ) a1 + a2

S3311 = 0
S1133 =

1
2 a2
2(1 ) a1 + a2

S 2211 =

1 a12
a1
(1 2 )

2
2(1 ) (a1 + a2 )
a1 + a2

S3322 = 0
S1212 =

1 a12 + a22
1 2
+

2
2(1 ) 2(a1 + a2 )
2

S 2323 =

a1
2(a1 + a2 )

S 3131 =

a2
2(a1 + a2 )

## The stress inside the inclusion is

11 =
1

a 2 + 2a1 a 2
a2
2 + 2
+
2

(a1 + a 2 ) a1 + a 2

2 a1
33*

1 a1 + a 2

*
11 +

a 22
a2

(a + a )2 a + a
1
2
2
1

*
22

a 2 + 2a1 a 2
a1
2 + 1
+
2

(a1 + a 2 ) a1 + a 2

2 a 2
33*

1 a1 + a 2

*
22 +

a12
a1

2
(a + a )
a1 + a 2
2
1

*
11

22 =

33 =

2 a1
2 a 2
2 *
*

11*
22
33
1 a1 + a 2
1 a1 + a 2
1

12 =

a2
a1 a 2
2
*
23
* , 23 = 2
2 12
a1 + a 2
1 (a1 + a 2 )

31 = 2

a1
31*
a1 + a 2

## Penny shape ( a1 = a2 >> a3 ):

I1 = I 2 = 2 a3 a1 , I 3 = 4 2 2 a3 a1
I12 = I 21 = 3 2 a3 4a13

4 2 a3 2
a1
=
=
=
=

I13 I 23 I 31 I 32 3
3
a
1

I11 = I 22 = 3 2 a3 4a13 , I 33 =

4
a32
3

S1111 = S 2222 =

13 8
a
1 2 a3
3 , S 3333 = 1
32(1 ) a1
1 4 a1

S1122 = S 2211 =

8 1
a
2 1 a3
3 , S1133 = S 2233 =

32(1 ) a1
8(1 ) a1

S3311 = S3322 =

4 + 1 a3
1

1
a1
8

S1212 =

1 2 a3
7 8
a

3 , S1313 = S 2323 = 1 +
2 1 4 a1
32(1 ) a1

S kk11 = S kk 22 =

1 2 a3
1 2 a3

, S kk 33 = 1
+
1 4 a1 1
1 2 a1

When a3 0 ,

I1 = I 2 = 0 , I 3 = 4
I12 = 0 , I 23 = 4 a22 , I 31 = 4 a12
I11 = I 22 = 0 , a32 I 33 = 4 3
S 2323 = S3131 =
S 3311 = S 3322 =

1
2

S3333 = 1
All other S ijkl = 0

## Flat ellipsoid ( a1 > a2 >> a3 ):

I1 =

4 a2 a3 {F(k ) E(k )}
a12 a22

I2 =

4 a3 E (k ) 4 a2 a3 {F(k ) E (k )}

a2
a12 a22

I 3 = 4

I12 =

4 a3 E(k )
a2

a12 a22

I 23 =
a22
I 31 =

## 4 4 a3 E(k ) a2 4 a2 a3 (F(k ) E(k )) a12 a22

a12

I 33 =

4
3a32

where F(k ) and E(k ) are the complete elliptic integrals of the first and the second kind,
5

respectively,

E (k ) =

F(k ) =

(1 k

sin 2

(1 k

sin 2

12

1 2

## k 2 = a12 a22 a12

Oblate spheroid ( a1 = a2 > a3 ):
12
2 a12 a3 1 a3 a3 a32
1
I1 = I 2 =
cos
32
a1 a1 a12
a12 a32

I 3 = 4 2 I1

I11 = I 22 = I12
I12 =

2
1

I13 = I 23 =

1
I I

I13 = 2 12 3 2
4
a1 4 a3 a1

4
I1 I 3
, 3I 33 = 2 2 I13
2
2
a3
a3 a1

## Prolate spheroid ( a1 > a2 = a3 ):

12
2 a1a32 a1 a12
a
2 1 cosh 1 1
I 2 = I3 =

3
2
a3
a12 a32 a3 a3

I1 = 4 2 I 2 , I12 =

4
I 2 I1
, 3I11 = 2 2 I12
2
2
a1
a1 a2

I 22 = I 33 = I 23
3I 22 =

I I
4
I I

I 23 22 12 , I 23 = 2 22 1 2
2
a2 4 a1 a2
a2
a1 a2